2019
DOI: 10.1016/j.chom.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Strain- and Species-Level Variation in the Microbiome of Diabetic Wounds Is Associated with Clinical Outcomes and Therapeutic Efficacy

Abstract: Highlights d Wound microbiota was profiled longitudinally in patients with diabetic foot ulcers d Staphylococcus aureus strains were associated with poor outcomes d S. aureus and other wound isolates promoted differential wound healing responses d Debridement depleted anaerobic bacteria in wounds with favorable outcomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
270
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(287 citation statements)
references
References 58 publications
13
270
1
3
Order By: Relevance
“…Alcaligenes faecalis is an aerobic Gram-negative nosocomial pathogen (20,21) that is generally regarded as a colonizer rather than a causative pathogen (22). However, recent research has explored its role in wound exacerbation (23). We hypothesize that the presence of Alcaligenes might interfere with the growth of other readily culturable microbes, providing the illusion of culture-negative results.…”
Section: Discussionmentioning
confidence: 99%
“…Alcaligenes faecalis is an aerobic Gram-negative nosocomial pathogen (20,21) that is generally regarded as a colonizer rather than a causative pathogen (22). However, recent research has explored its role in wound exacerbation (23). We hypothesize that the presence of Alcaligenes might interfere with the growth of other readily culturable microbes, providing the illusion of culture-negative results.…”
Section: Discussionmentioning
confidence: 99%
“…While the role of eosinophils and their cross-talk with mast cells during wound healing are poorly understood, our data demonstrate that the presence of eosinophils specific for DFUs may have a role in contributing to the wound chronicity. Furthermore, Staphylococcus aureus the most prevalent pathogen in both DFU 62 and atopic dermatitis 63 has shown to be responsible for increased recruitment of mast cells and eosinophils in animal models of atopic dermatitis 64 , suggesting similar traits in DFUs.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither patient demographics nor wound type influenced the bacterial composition of the chronic wound microbiome [ 17 ]. Different studies have described this DFU microbiota [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Although they have produced interesting results and confirmed that the microbiota is a highly dynamic microbial community that maintains a relationship with the host, understanding the complex competitive or synergistic interaction between commensal and pathogenic microorganisms is necessary as it could play an important role in the severity and evolution of the wound.…”
Section: Pathophysiology Of Diabetic Foot Ulcersmentioning
confidence: 99%